Disability and the Unionized Workplace - Mason Ameri; Mohammad Ali; Lisa Schur; Douglas L. Kruse (Institute of Labor Economics (IZA), 2019)
The employment of people with disabilities has received significant attention, but little is known about how unions affect their employment experiences. To address this, we analyze monthly U.S. Current Population Survey (CPS) data from 2009 through 2017 and find that the unionization rate declined more rapidly among employees with disabilities. The results are not due to demographic or occupational factors, but to the lower rate at which people with disabilities are hired into unionized jobs. This lower hiring rate more than offsets the greater job retention of unionized workers with disabilities. Given that employers generally control hiring, it appears they are particularly reluctant to hire people with disabilities into jobs with union protections. Overall, in the union context, workers with disabilities appear more likely to be "last hired," but less likely to be "first fired." We also find that a union wage premium of 29.8% for workers with disabilities is greater than the 23.9% premium for workers without disabilities. There remains a pay gap of -5.7% between union workers with and without disabilities, compared to a -10.1% pay gap between non-union workers with and without disabilities. Exploratory data reveal that both union coverage and disability status increase the likelihood of requesting accommodations, supporting the voice model of unions. Overall the results indicate that while unions appear to help workers with disabilities in the U.S., unionized positions are becoming less available to workers with disabilities.
Keywords: J14; J51; J31; 330; disability; unions; wage differentials; job mobility